An integrated tool for microarray data clustering and cluster validity assessment - Bolshakova, Nadia; Azuaje, Francisco; Cunningham, Pádraig (Bioinformatics, 2005)
In this paper we present a data mining system, which allows the application of different clustering and cluster validity algorithms for DNA microarray data. This tool may improve the quality of the data analysis results, and may support the prediction of the number of relevant clusters in the microarray datasets. This systematic evaluation approach may significantly aid genome expression analyses for knowledge discovery applications. The developed software system may be effectively used for clustering and validating not only DNA microarray expression analysis applications but also other biomedical and physical data with no limitations. Availability: The program is freely available for non-profit use on request at http://www.cs.tcd.ie/Nadia.Bolshakova/Machaon.html Contact: Nadia.Bolshakova@cs.tcd.ie